IMPLEMENTATION OF DIFFERENTIATED LEARNING TO IMPROVE LEARNING OUTCOMES ON THE EARTH AND SOLAR SYSTEM MATERIAL FOR JUNIOR HIGH SCHOOL GRADE VII - Muflichatu Nur Fita; Indra Fardhani; Erna Mudyah Rahayu (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2023)
This study aims to determine the application of differentiated learning based on learning styles on the material of the Earth and the Solar System on student learning outcomes. This research is a Classroom Action Research (PTK) which was carried out in two cycles, namely Cycle I and Cycle II with each cycle consisting of four stages, namely planning, action, observation, and reflection. Instruments in classroom action research used observation sheets of teacher and student activities and multiple choice written test sheets. Data collection techniques in the form of observation and written tests. The data analysis method used is quantitative for the analysis of learning outcomes and qualitative for the results of observations. The results showed that the completeness of the classical learning outcomes was initially 0% at the pre-cycle stage, then increased to 37,50% in Cycle I, and reached 78.13% in Cycle II after applying the differentiated approach. These findings indicate that differentiated learning has a positive impact on improving the completeness of students' classical learning outcomes in the context of this research.